Administrative Data Censuses in US States - Amy O'Hara (International Journal of Population Data Science, 2019)
This paper describes work underway to conduct administrative data censuses in several US states. We are helping states identify sources that, when combined, reflect their entire population, and introduce approaches to efficiently and routinely integrate their data.